1997
DOI: 10.1111/j.1365-2494.1997.tb02363.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an inoculant/enzyme preparation as an additive for grass silage for dairy cattle

Abstract: Herbage from the first regrowth of perennial ryegrass-based swards was directly ensiled after treatment with a bacterial inoculant/enzyme preparation (SIL-ALL, Alltech UK) at 3·0 l t Ϫ1 , formic acid (850 g kg Ϫ1 ) at 2·59 l t Ϫ1 or no additive (Control). The mean dry matter (DM) and water-soluble carbohydrate concentrations of the grass were 185 and 24·0 g kg Ϫ1 (fresh basis) respectively. Lactic acid concentrations after ensiling increased at a lower rate in formic acid-treated herbage than with the other tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…While, cows fed un-treated silage recorded the lowest (P< 0.05) DM silage intake. These results were inagreement with Petterson et al, (1997) who found that DM intake increased with silage containing lower percentage of acetic acid. Many studies have been reported a positive effect of formic acid and bacterial inoculants on increased silage intake and a beneficial effect on cattle performance Zwi (2003).…”
Section: Resultssupporting
confidence: 56%
“…While, cows fed un-treated silage recorded the lowest (P< 0.05) DM silage intake. These results were inagreement with Petterson et al, (1997) who found that DM intake increased with silage containing lower percentage of acetic acid. Many studies have been reported a positive effect of formic acid and bacterial inoculants on increased silage intake and a beneficial effect on cattle performance Zwi (2003).…”
Section: Resultssupporting
confidence: 56%
“…No difference was noted in the DM and TDN intake between HI and HC, which may have been due to the absence of an increase in the DM intake of HI, not leading to an increase in the TDN intake, although the TDN content increased. Regarding the DM intake of silage with the addition of inoculant, Winters et al [43] reported an increase in the intake of Italian ryegrass silage, whereas no increases in the intake of perennial ryegrass, alfalfa, and mixed-seeded grass and legume silage were reported by Patterson et al [44], Kung et al [45], and Stokes [46], respectively, showing no consistent tendency. Since the DCP and TDN contents, and DCP intake of HI were higher than those of SC and SI, silage with the high DCP and TDN contents, and DCP intake may have been prepared by the addition of inoculant to the high-CP grass material.…”
Section: Discussionmentioning
confidence: 95%